Komunikasi Kelompok Belajar - Musliati, Musliati (Prophetica : Scientific and Research Journal of Islamic Communication and Broadcasting, 2020)
This article discusses study group communication in terms of how effective communication is built in study groups and finds out what factors affect learning achievement and the advantages and disadvantages of study groups by analyzing the process. The research method is qualitative, namely the collection of data using analysis and description of the existing reality by analyzing and collecting literature such as books and journals, then re-examined and concluded in articles. In communicating effectively with study groups, it is necessary to have basic guidelines used so that the group process can run well and in an orderly manner, and to build a guideline for each member to work together. The basic guidelines used are to be an attentive listener and an active contributor, don’t belittle others, promise to be respectful in completing tasks and sharing responsibilities. The goal is that group learning can run well. Keywords: communication 1; study group 2; Study 3